EFISIENSI PRODUKSI SISTEM USAHATANI PADI PADA LAHAN SAWAH IRIGASI TEKNIS - DEWI SAHARA; IDRIS - (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2007)
Product efficiency of lowland rice field farming system research had been conductedin technical irrigation on July to November 2005 in Uepai, Konawe district, SoutheastSulawesi province. Purposive sampling was used to choose location based on AgroEcological Zone (AEZ). This research aimed to know farmer’s rationality in using productionfactor. Multiple regression linear was used to analysis the factors influencing production andwas continued by allocate efficiency test. The result showed that harvest area, pesticide, andlabors have positive effect on production factors. Then, to find maximum benefit, farmerneeded reduce the use of SP-36 fertilizer. Therefore, to reach both optimum production andadvantage need to extend harvest area, addition of pesticide and labor, and to reduce SP-36fertilizer dosage.